2017
DOI: 10.1136/bmjopen-2016-013873
|View full text |Cite
|
Sign up to set email alerts
|

Translation, adaptation and validation of two versions of the Chronic Liver Disease Questionnaire in Malaysian patients for speakers of both English and Malay languages: a cross-sectional study

Abstract: ObjectiveWe aimed to adapt, translate and validate the Chronic Liver Disease Questionnaire (CLDQ) in Malaysian patients with chronic liver diseases of various aetiologies.SettingTertiary level teaching institution in Malaysia.ParticipantsThe validation process involved 211 adult patients (English language n=101, Malay language n=110) with chronic liver disease. Characteristics of the study subjects were as follows: mean (SD) age was 56 (12.8) years, 58.3% were male and 41.7% female. The inclusion criteria were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
3
4
0
2
Order By: Relevance
“…This observation strongly supports the construct validity of the CLDQ‐SG for the assessment of severity of liver disease in the different groups of CLD patients. Our findings are consistent with similar studies of translation and validation of the CLDQ in various ethnic populations . Clinicians can thus rely on the CLDQ‐SG to assess the deterioration of HRQOL as CLD progresses.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This observation strongly supports the construct validity of the CLDQ‐SG for the assessment of severity of liver disease in the different groups of CLD patients. Our findings are consistent with similar studies of translation and validation of the CLDQ in various ethnic populations . Clinicians can thus rely on the CLDQ‐SG to assess the deterioration of HRQOL as CLD progresses.…”
Section: Discussionsupporting
confidence: 90%
“…The predominant etiology of CLD was chronic hepatitis B, which accounted for 78.9% of cases, in keeping with the expected etiological spectrum in the Singapore population . The median duration of CLD was 9 years from the date of first diagnosis, with a range of 5–17 years.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Janani et al 31 reported that SF-36 and CLDQ scores were lower in cirrhosis patients with Child-Turcotte-Pugh class C, and CLDQ score was lower in younger patients (≤45 years). Khairullah & Mahadeva 32 reported that CLDQ scores were significantly lower for patients with decompensated cirrhosis compared to compensated or no cirrhosis. In this study, there were differences in SNAC total scores according to disease stage and patient's age which supports known group validity.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Liver Disease Questionnaire (CLDQ) as a useful PRO for measuring HRQOL in patients with CLD 8 . CLDQ is known to correlate with liver reserve function such as Child‐Pugh classification, and its usefulness and reliability to assess HRQOL in patients with CLD have been confirmed in various ethnicities, liver disease etiologies, regions and countries around the world, 9–14 including in Japanese patients 15,16 . It involves 29 questions categorized into six domains, abdominal symptoms (AS), fatigue (FA), emotional functions, worry (WO), activity (AC), and systemic symptoms (SS).…”
Section: Introductionmentioning
confidence: 99%